2013
DOI: 10.4103/1596-3519.108242
|View full text |Cite
|
Sign up to set email alerts
|

NeuroAIDS in sub-Saharan Africa: A clinical review

Abstract: NeuroAIDS affects half of the 22 million people currently living with HIV/AIDS in sub-Saharan Africa, where cryptococcal meningitis alone is responsible for 504,000 deaths annually. A good understanding of NeuroAIDS may help improve disease-free survival in patients at risk and optimize resource utilization by caregivers. In this review, we aimed to provide a summary of major NeuroAIDS syndromes of relevance in Africa. We searched Medline for English language literature to identify relevant publications, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 86 publications
0
14
0
2
Order By: Relevance
“…However, recent clinical studies and a meta-analysis [1,166,167] in patients on HAART revealed milder forms of neurological dysfunction (ANI & MND) in greater than half of HIV-positive patients. In studies examining individuals with ART-controlled HIV viremia, HIV DNA in PBMCs correlated with regional brain atrophy highlighting the contribution of peripheral viral reservoirs to CNS pathology [168].…”
Section: Treatment Modalities For Handmentioning
confidence: 99%
“…However, recent clinical studies and a meta-analysis [1,166,167] in patients on HAART revealed milder forms of neurological dysfunction (ANI & MND) in greater than half of HIV-positive patients. In studies examining individuals with ART-controlled HIV viremia, HIV DNA in PBMCs correlated with regional brain atrophy highlighting the contribution of peripheral viral reservoirs to CNS pathology [168].…”
Section: Treatment Modalities For Handmentioning
confidence: 99%
“…Sub-Saharan Africa is the most heavily affected region in the world with estimated 1.9 of the 2.5 million new HIV infections worldwide in 2011 [ 1 ]. Most of the fatal courses remain in the context of late diagnosis of HIV infection and delayed initiation of antiretroviral therapy (ART) [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…metástasis, tuberculosis) y no compresivas (ej. mielitis, paraparesia espástica tropical, mielopatía vacuolar) basados en la urgencia del manejo [33,34]; se estima que la mielopatía vacuolar afecta a un tercio de los portadores del VIH y causa molestias relevantes al 1-5% [35]. Los estudios neurofisiológicos han detectado Tabla 2.…”
Section: Discussionunclassified
“…A pesar de esto los resultados se aproximan a los obtenidos en estudios previos de otros sitios del mundo [3]. En la actualidad, los esfuerzos en investigación se enfocan en el ictus, leucoencefalopatía multifocal progresiva, demencia asociada al VIH y aumento de resistencia al tratamiento; sin embargo, se consideran problemas importantes la disponibilidad de fármacos, falta de programas de detección y derivados de la sociedad como la estigmatización y discriminación de los pacientes [34].…”
Section: Publonsunclassified